LINC00472 Acts as a Tumor Suppressor in NSCLC through KLLN-Mediated p53-Signaling Pathway via MicroRNA-149-3p and MicroRNA-4270 - Aimei Zou; Xingli Liu; Zongjiong Mai; Junke Zhang; Zhuohuan Liu; Qilu Huang; Aibing Wu; Chenyu Zhou (Elsevier, 2019)
Long non-coding RNAs and microRNAs (miRNAs) have been reported to participate in the progression of non-small-cell lung cancer (NSCLC). Long intergenic non-protein-coding RNA 472 (LINC00472), miR-149-3p, and miR-4270 were found to be involved in tumor activities, suggesting potential roles in NSCLC. Thus, this study aimed to examine the ability of LINC00472 to influence the progression of NSCLC with the involvement of miR-149-3p and miR-4270. Initially, differentially expressed long non-coding RNAs (lncRNAs), downstream regulatory miRNAs, and genes related to NSCLC were identified. Next, the interaction among LINC00472, miR-149-3p and miR-4270, and KLLN and the p53-signaling pathway was determined. The effect of LINC00472 on the expression of E-cadherin, N-cadherin, and Vimentin was examined through gain-of-function and loss-of-function experiments. Lastly, the effects of LINC00472 on NSCLC tumor growth were assessed in vivo. LINC00472 and KLLN were found to exhibit low levels, while miR-149-3p and miR-4270 were highly expressed in NSCLC. In addition, the overexpression of LINC00472 was observed to upregulate KLLN and activate the p53-signaling pathway, which ultimately inhibited the invasion, migration, and EMT of NSCLC cells via miR-149-3p and miR-4270, corresponding to decreased N-cadherin and Vimentin and increased E-cadherin. The overexpression of LINC00472 exerted an inhibitory effect on tumor growth in vivo. Taken together, the key evidence suggests that the overexpression of LINC00472 can downregulate miR-149-3p and miR-4270 to upregulate KLLN and activate the p53-signaling pathway, thus inhibiting the development of NSCLC. This study highlights the potential of LINC00472 as a promising therapeutic target for NSCLC treatment. Keywords: long intergenic non-protein-coding RNA 472, microRNA-149-3p, microRNA-4270, KLLN, p53-signaling pathway, non-small-cell lung cancer, invasion, migration, epithelial-mesenchymal transition